First report of Entamoeba moshkovskii in human stool samples from symptomatic and asymptomatic participants in Kenya - Cecilia Kyany’a; Fredrick Eyase; Elizabeth Odundo; Erick Kipkirui; Nancy Kipkemoi; Ronald Kirera; Cliff Philip; Janet Ndonye; Mary Kirui; Abigael Ombogo; Margaret Koech; Wallace Bulimo; et al. (Tropical Diseases, Travel Medicine and Vaccines, 2019)
Abstract Entamoeba moshkovskii is a member of the Entamoeba complex and a colonizer of the human gut. We used nested polymerase chain reaction (PCR) to differentiate Entamoeba species in stool samples that had previously been screened by microscopy. Forty-six samples were tested, 23 of which had previously been identified as Entamoeba complex positive by microscopy. Of the 46 specimens tested, we identified nine (19.5%) as E. moshkovskii-positive. In seven of these nine E. moshkovskii-positive samples, either E. dispar or E. histolytica (or both) were also identified, suggesting that co-infections may be common. E. moshkovskii was also detected in both symptomatic and asymptomatic participants. To the best of our knowledge, this is the first report of E. moshkovskii in Kenya.